A study on the economic, social, and personal factors influencing the decision of students to enroll in and continue with library and information science as an undergraduate course - Pasion, Dan Oliver C.; Aguirre, Vyva Victoria M. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2011)
According to the enrollment data from the School of Library and Information Studies of the University of the Philippines from the 1st semester of SY 2007-2008 to 1st semester of SY 2010-2011, there was a decline of freshmen students and increase of shiftees and transferees who enrolled in the Library and Information Science course. This may be attributed to a variety of reasons, one of the most important of which is the School's admission requirements. However, the researcher believes that perceptions play a key role in the decision of students, especially those of university students who have already gained additional experiences in their few months or years of staying in the university. In other words, negative perceptions influence the decision of students not to enroll in an LIS course and positive perceptions gained through experiences influence the decision of students to enroll in, remain and complete the course.
A total of 328 LIS students were surveyed. Seventy were from the University of the Philippines School of Library and Information Studies. One hundred twenty-nine were from the LIS Department under the College of Education in University of Santo Tomas. The last 129 were from the LIS Department under the College of Arts in Polytechnic University of the Philippines. The self-structured survey questionnaire was composed of open-ended questions designed to extract a student's true reason for enrolling in and continuing with the course, and their perceptions about the course. This was supplemented by scale items such as ranking and Likert scales.
Data gathered from the survey questionnaires revealed economic factors that influenced the decision of students to enroll in and continue with the course such as job opportunities here and abroad, licensure examination; social factors such as relatives and friends who took up or were taking up LIS, and recommendation from their former or current schools; lastly, personal factors such as interest in IT and the need to graduate. Reasons for enrollment and continuation of the course were the same for the three universities with the exception of those who knew nothing about the course when they enrolled and those who opted to shift to another course. Those who knew nothing but still enrolled in the course continued because they learned to appreciate, enjoy, like, and love the course. Those who opted to shift were affected by their friends who looked down or had negative perceptions on the course. Except for those who shifted, findings also revealed how perceptions and stereotypes did not influence students to enroll in and continue with the course. Perceptions were well-diverse in UP, ranging from positive perceptions to neutral to strongly negative. Perceptions were very limited to traditional perceptions in UST though they also had strong negative perceptions. Perceptions were leaning towards negative in PUP.
Recommendations included activities that can be done by librarians, LIS professors, and LIS students such as seminars, career talks, career orientations, and library tours addressed to students, parents, and school administrators. Expansion of course outlines such as adding more hands-on activities and library visits were also recommended.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Library science as a profession; Library science -- Vocational guidance